Assessing service use for mental health by Indigenous populations in Australia, Canada, New Zealand and the United States of America: a rapid review of population surveys - Cecily McIntyre; Meredith G. Harris; Amanda J. Baxter; Stuart Leske; Sandra Diminic; Joseph P. Gone; Ernest Hunter; Harvey Whiteford (BMC, 2017)
Abstract Background Indigenous people in Australia, Canada, New Zealand and the United States of America experience disproportionately poor mental health compared to their non-Indigenous counterparts. To optimally allocate resources, health planners require information about the services Indigenous people use for mental health, their unmet treatment needs and the barriers to care. We reviewed population surveys of Indigenous people to determine whether the information needed to guide service development is being collected. Methods We sought national- or state-level epidemiological surveys of Indigenous populations conducted in each of the four selected countries since 1990 that asked about service use for mental health. Surveys were identified from literature reviews and web searches. We developed a framework for categorising the content of each survey. Using this framework, we compared the service use content of the surveys of Indigenous people to each other and to general population mental health surveys. We focused on identifying gaps in information coverage and topics that may require Indigenous-specific questions or response options. Results Nine surveys met our inclusion criteria. More than half of these included questions about health professionals consulted, barriers to care, perceived need for care, medications taken, number, duration, location and payment of health professional visits or use of support services or self-management. Less than half included questions about interventions received, hospital admissions or treatment dropout. Indigenous-specific content was most common in questions regarding use of support services or self-management, types of health professionals consulted, barriers to care and interventions received. Conclusions Epidemiological surveys measuring service use for mental health among Indigenous populations have been less comprehensive and less standardised than surveys of the general population, despite having assessed similar content. To better understand the gaps in mental health service systems for Indigenous people, systematically-collected subjective and objective indicators of the quality of care being delivered are needed.